2021
DOI: 10.1186/s12879-021-06793-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leakage in dengue: a systematic review of prospective observational studies

Abstract: Plasma leakage is a precursor to life-threatening complications of dengue, but this group is poorly defined and not often reported in literature. Patients with Dengue haemorrhagic fever (DHF) as defined in the 1997 World Health Organization classification are often reported, and they all have plasma leakage, but some patients with plasma leakage do not meet the definition of DHF. The study aims to estimate the frequency of plasma leakage and DHF (as a surrogate of plasma leakage) in dengue and its variations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 73 publications
1
13
0
1
Order By: Relevance
“…In addition, the definition and development of criteria for diagnosing plasma leakage have long been neglected, resulting in challenging and underreporting of plasma leakage. It is recommended that standardization of diagnosis and reporting of plasma leakage should be a research priority for dengue [ 31 ]. Moreover, we found that patients with hemorrhage were more likely to develop severe dengue than those without hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the definition and development of criteria for diagnosing plasma leakage have long been neglected, resulting in challenging and underreporting of plasma leakage. It is recommended that standardization of diagnosis and reporting of plasma leakage should be a research priority for dengue [ 31 ]. Moreover, we found that patients with hemorrhage were more likely to develop severe dengue than those without hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…There were no deaths in our cohorts to replicate these findings. Death is a rare outcome in dengue (<1%), even amongst hospitalised patients who have more severe disease [ 6 ]. Other studies used ML to predict adverse outcomes in dengue using genomics and transcriptomics data [ 39 , 40 ], the findings however are of limited value to clinicians managing patients for bed-side risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Considering all these factors we selected plasma leakage as the optimal outcome for risk prediction since it is a single criterion that can be objectively measured, and complications of dengue mostly (except for rare instances of abnormal bleeding) occur in patients who have plasma leakage. Given the dependence on WHO based classifications most dengue studies do not report incidence plasma leakage as a stand-alone figure but estimates from available literature suggests that 36.8% (95% CI: 35.4–38.2%) of all dengue patients have this outcome [ 6 ]. Thus, predicting this subgroup accurately can be a cost saver by reducing duration of hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations